Konsumsi sayur dan buah dalam upaya mencegah penyakit tidak menular - Kurniati, Ardesy Melizah; Tamzil, Nia Savitri; Dalilah, Dalilah; Prasasty, Gita Dwi; Suciati, Tri; Muhammad, Fadhil; Fitrianti, Fitrianti (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Hypertension and obesity are one of the risk factors for the increasing number of non-communicable diseases. In Indonesia, in 2018 there was an increase in cases of non-communicable diseases where there were five diseases that were included as the largest cause of death. There were heart disease, cancer, and diabetes. Some of the risk factors that cause an increase in cases of non-communicable diseases include high consumption of sugar/salt/fat, smoking habits, lack of physical activity, and lack of consumption of fruits and vegetables. This study aims to determine the picture of body mass index and blood pressure as well as the portion of fruit and vegetable consumption in the community in Kelurahan 20 Ilir D-IV Palembang. In this study, there were 33 respondents consisting of 10 men and 23 women, with an age range of 23-76 years. A total of 18 respondents (54.5%) were overweight, and as many as 13 (39.4%) and 12 (36.4%) respondents had 1st degree of hypertension and pre-hypertension respectively. Of the average portions of vegetable and fruit consumption in 1 meal, as many as 15 (45.4%) and 10 (30.3%) respondents consumed less vegetables and fruits. This study shows that there were people that consume fruits and vegetable in fewer portions and have overweight and 1st degree hypertension.